(untitled) (Clinics, 2020)
OBJECTIVES: To investigate the effects of an intratympanic injection of dexamethasone combined with gentamicin on the expression level of serum P0 protein antibodies in patients with Meniere’s disease (MD). METHODS: A total of 136 patients with MD treated in our hospital were enrolled in this study. Among them, 68 patients were treated with an intratympanic injection of dexamethasone combined with gentamicin (observation group). Another 68 patients were treated with gentamicin alone (control group). RESULTS: After treatment, the expression levels of IgG and IgM in the two groups significantly decreased (po0.05); the levels in the observation group were significantly lower than those in the control group (po0.05). The incidences of vertigo, tinnitus, and gait instability in the observation group were significantly lower than those in the control group (po0.05). Vestibular symptom index (VSI) scores in the observation group were significantly lower than those in the control group (po0.05). We observed no significant difference between the two groups in the number of vertigo attacks 6 months after treatment (p40.05). CONCLUSION: For patients with MD, dexamethasone combined with gentamicin can reduce the incidence of vertigo, tinnitus, and gait instability, but it has no effect on the efficacy or number of vertigo attacks 6 months after treatment. Therefore, the levels of myelin P0 protein antibodies after treatment can be used as predictors of vertigo at 6 months after treatment.